2006
DOI: 10.1007/s10643-006-0081-3
|View full text |Cite
|
Sign up to set email alerts
|

Using Collaborative Assessment to Examine the Relationship between Self-Reported Beliefs and the Documentable Practices of Preschool Teachers

Abstract: A team of researchers used a collaborative assessment protocol to compare the self-reported teaching beliefs of a convenience sample of preschool teachers (N = 57) to their documentable practices (i.e., practices that could be observed, recorded, and categorized using a deductive strategy). Data were examined from survey instruments, detailed classroom observations and time-sampling, curriculum materials, and program artifacts. Results indicated that when child-directed choice/play time, emergent literacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 12 publications
(11 reference statements)
1
39
0
8
Order By: Relevance
“…Our results also support the work by McMullen et al (2006) and Stipek and Byler (1997) on how ECEs' beliefs inform their practices. In both these studies and in the current study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results also support the work by McMullen et al (2006) and Stipek and Byler (1997) on how ECEs' beliefs inform their practices. In both these studies and in the current study.…”
Section: Discussionsupporting
confidence: 86%
“…For infants who are not yet verbal, ECEs need to be sensitive to the child's communication and to do this they need to understand early communication development and develop a relationship with the child in order to interpret their signals and facilitate their communication development (Albers et al, 2007) ECEs' beliefs about child development and education inform their practice (McMullen, 1999;McMullen et al, 2006;Stipek & Byler, 1997). From their study comparing self-reported beliefs of preschool teachers with data from an assessment protocol, McMullen et al (2006) found that information about child development and education strategies were filtered through educators' personal belief systems. Stipek and Byler (1997) also explored the beliefs and practices of 60 educators from preschool through to primary school, finding that beliefs played an important role in programming for the ECEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the situations where teachers identified themselves as leaders, they were dissatisfied with the available learning environments-specifically, classroomsand with the dilemmas they face in attempting to integrate curriculum with play. The complaints posed by them relate to teaching as a technical act (Moje & Wade, 1997), or as a "traditional" or academic-oriented process, including dominant behavior such as consistent routines, pre-planned curriculums, and teacher-directed learning (McMullen et al, 2006).…”
Section: Discussion With Students During Teacher Educationmentioning
confidence: 99%
“…These notes will also be coded according to c-c and t-d as well as DAP and di. McMullen et al (2006) conducted a similar study in which the researchers compared teacher's beliefs with their practices. They started with a survey for participating teachers to complete.…”
Section: Methods Of Proceduresmentioning
confidence: 99%